UPAYA PENGEMBANGAN TAMAN MONYET SEBAGAI ASSET PEMERINTAH BANDAR LAMPUNG - Rieka Ramadhaniyah; Herlina Herlina (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
The purpose of this research is to contribute in the efforts to attract domestic and foreign tourists to visit the monkey park forest of considerable potential as a tourist attraction, create jobs and reduce theunemployment rate in the area. Raising revenue Lampung Bandar Lampung city government especially 23 in the tourism sector. Population in Bandar Lampung penenlitian is a community with a sample of 400 respondents.Hypothesis 1, 4, 5, 6 and 7 are Ho accepted means all has no significant effect, while for hypothesis 2 and 3 is Ha accepted means all there is significant influence. result the coefficient of determination R Square of 0.014 or 14%, this indicates that that variable aspects of tourism development (X2) is affected by the tourism development concept variables (X1) while the remaining 81.6% influenced by other factors. this suggests that government asset variable Bandar Lampung (Y2) is affected by the tourism development concept variables (X2) and tourism development efforts (Y1) with a percentage value obtained was 54.9% while the remaining 36.1% influenced by other factors in addition to the variable aspects - aspects of tourism development (X2) and tourism development efforts (Y1).